OPTIMALISASI PEMANFAATAN HARTA WARISAN : KUNCI MENINGKATKAN EKONOMI KELUARGA - Windatria Windatria; Malahayatie Malahayatie; Taufiq Taufiq (JSE: Jurnal Sharia Economica, 2026)
The distribution of wealth in Islam is a strategic instrument for achieving social justice and equitable welfare. One important mechanism in this distribution is the inheritance system (faraidh), which not only functions as a mechanism for transferring wealth between generations, but also as a means of maintaining economic balance and family harmony. This study aims to analyze the optimization of inheritance utilization in supporting family economic empowerment and to identify various challenges faced in its management. This study uses a qualitative approach based on literature review by examining various research results related to productive inheritance management. The results of the study show that transparent, fair, and Sharia-compliant inheritance management has the potential to improve the welfare of heirs, strengthen family solidarity, and create sustainable business opportunities. However, a lack of understanding of faraidh law, conflicts between heirs, and weak legal documentation are major challenges that often hinder the optimization of inheritance assets. Therefore, education, open communication, and professional asset management are needed so that inheritance assets can contribute maximally to the economic development of the community.